VIH/SIDA: COMPORTAMIENTO EPIDEMIOLÓGICO DE LA TRANSMISIÓN VERTICAL EN EL CONTEXTO GENERAL DE LA INFECCIÓN EN CHILE. - Valdés R., Enrique; Sepúlveda M., Alvaro; Candia P., Paula; Sepúlveda B., Carolina; Lattes A., Karinna (Revista Chilena de Obstetricia y Ginecología, 2011)
Background: The risk of transmitting HIV from mother to unborn child, without any antiretroviral prophylaxis, reaches 30%. It can be reduced to less than 2% by implementing integral preventive strategies. Objective: To assess the epidemiological profile of HIV vertical tranengsmission in Chile since the implementation of the national AIDS transmission prevention program. Method: Data from the Epidemiology Department of the Health Ministry and the National Commission for AIDS grouped by year, location, age and gender. With special emphasis on vertical transmission. Results: 9317 cases of HIV infection and 7886 cases of AIDS have been reported in Chile (1984-2006), with a decreasing tendency since 2003. Sexual exposure continues to be the primary route with 93.4% of the cases. The male/female ratio for case notification is 4:1, with a rising tendency among women. The most affected is between 20-39 years old (73% HIV notification and 63.1% for AIDS). Among children between 0-9 years of age is 1.1% of the HIV and 1.4% of AIDS notifications, all of them for vertical transmission. Conclusions: HIV vertical transmission in Chile is responsible for a small percentage of HIV/AIDS notifications, but it accounts for all of the infected children. There's been an important reduction in this transmission route, reaching prevalence close to the aimed rates, which can explained by the expanding prevention programs of the health policies implemented by the Health Ministry.